Draft Annual Plan 2006-07 Volume-II Karnataka - Planning Commission (Planning Commission, 2005)
Draft Annual Plan 2006-07 Proposed Outlays - Outlay by Major Heads of Develop, Draft Annual Plan 2006-07 Proposed Outlays - Scheme wise allocation, Physical Targets and Achievements, Statement Regarding External Aided Project, Details of Internal and Budgetary Resources of State Level Public Enterprises, Bharath Nirman Programmes, Draft Annual Plan (2006-07) Outlay by Heads of Developments for District Plans, Centrallay Sponsored Scheme, Draft Annual Plan (2006-07) - Financial Outlays for TSP, Draft Annual Plan (2006-07) - Physical Targets for TSP
Planning and Statistics Department Karnataka